Case report: Surgical treatment and literature review of a recurrent case of glucagonoma - Liu, Zhipeng; Yang, Faji; Hao, Yijie; Jiang, Qirong; Zhang, Yisu; Zheng, Qixuan; Jiang, Yupeng; Lu, Jun; Gao, Hengjun (Frontiers in Oncology, 2024)
A 40-year-old male patient was admitted due to abdominal distension and discomfort in the upper abdomen persisting for three days. Enhanced CT of the upper abdomen revealed an irregularly dense soft tissue area in the body and tail of the pancreas, approximately 7.6 × 3.1 cm in size, with blurred boundaries, and indistinct separation from the splenic artery and vein. Multiple liver lesions of varying sizes and slightly lower densities were also observed. Liver tumor biopsy considering a neuroendocrine tumor G2, combined with the medical history, led to a diagnosis of pancreatic neuroendocrine tumor G2 with liver metastasis. Physical examination showed mild tenderness in the upper abdomen but no other significant positive signs. During treatment, the patient developed multiple red papular rashes around the mouth, on both lower limbs, and the perineum, accompanied by itching. The glucagon level was 1138.3 pg/L. The patient underwent resection of the pancreatic body and tail, splenectomy, partial liver tumor resection, and cholecystectomy. Within five days post-surgery, the skin lesions began to crust and flake off. On the 14th day post-surgery, the serum glucagon level was rechecked at 136.4 pg/L. As of April 2024, progression of liver lesions was noted, with no significant skin symptoms during the period.(GCGN) is a rare pancreatic neuroendocrine tumor (pancreatic neuroendocrine tumor，pNET) originating from pancreatic islet A2 cells, whereby the islet cells secrete abundant glucagon[1]. The estimated annual incidence of glucagonoma is ~1 case per 20,000,000 individuals[2]. Consequently, there is limited research and reporting on GCGN within China. GCGN typically occurs in the body and tail of the pancreas and is often accompanied by liver metastasis [3]. The classic clinical features of GCGN include migratory necrolytic erythema, perioral dermatitis/glossitis, and diabetes. The low incidence rate and the lack of early characteristic symptoms can easily lead to misdiagnosis of GCGN, adversely affecting diagnosis, treatment, and prognosis. This paper aims to report on a case of GCGN with liver metastasis treated by the